Corrosion characteristics of laser-cleaned surfaces on iron artefact - Biljana M. Bobić; Suzana Polić (Zaštita Materijala)
Nd:YAG laser was used for cleaning surfaces of cultural heritage iron artefacts covered with corrosion products. The corrosion products were removed without damaging the base material. Three different electrochemical techniques were used for the determination of the corrosion rate of mechanically prepared iron, laser-cleaned iron and laser-cleaned iron with Paraloid B44 coating. The morphology of the tested surfaces was analysed by SEM. The linear polarization resistance technique, electrochemical impedance spectroscopy and linear sweep voltammetry have shown that the corrosion rate of the laser-cleaned iron is approximately 50 % higher than the corrosion rate of the mechanically prepared iron. Electrochemical impedance spectroscopy has shown that the pore resistance of the Paraloid coating on the laser-cleaned iron sample decreases at the beginning of the test and remains approximately constant after this period. At the beginning of the test, the charge transfer resistance value is constant and then decreases rapidly i.e. the corrosion rate of the iron in the Paraloid coating pores increases with time. During the linear sweep voltammetry test of the iron sample with Paraloid coating, it was noticed that the anodic polarisation curve shows an unusual shape at the potentials more positive than - 0.5 V.